Toxicidade de fungicida comercial a base de tebuconazol em Danio rerio - Castro, Tássia Flávia Dias (2016)
This work aimed at evaluating the effects of the exposure to different concentrations of tebuconazole, active principal for commercial fungicides, over Danio rerio embryos and adults, by means of anxiety, glucose, DNA damage and embryonic development trials. Two trials were conducted, the first with adults, aiming at evaluating stress parameters by means of new tank dive, plasma glucose and genotoxicity tests, as well as micronuclei test and comet trial. In the second trial, we evaluated the toxicity of the fungicide, influencing the embryonic development of zebrafish. In trial 1, 320 specimens of adult D. rerio, divided into 8 tanks, having been exposed to the concentrations of 0, 100, 200 and 300 µg/L of tebuconazole, with the respective replicates at times 24, 72 and 96 hours. After each period of exposure, 10 animals were removed from each tank, taken to filming of the new tank dive test having, subsequently, collected blood and gill samples to conduct the remaining tests. In trial 2, zebrafish embryos were exposed to the concentrations of 0, 12.5, 25, 50, 100 and 200 µg/L of tebuconazole for a period of 96 hours, daily analyzing morphological changes and survival rate. The results show a behavioral deviation of the zebrafish, when the animals exposed to tebuconazole were more anxious, reducing the time of permanence at the surface of the tank. For plasmatic glucose (mg/dL) there was no significant difference (p>0.05). For the micronuclei test and comet trial, the exposure to tebuconazole resulted in a significant increase (p<0.05) of damage to the DNA in function of the time of exposure and different concentrations of tebuconazole. For the embryos, the tebuconazole caused no malformation during the embryonic stages. The survival rates were not alter ed with the doses of 12.5, 25 and 50 µg/L. Only the dose of 100 µg/L was capable of decreasing the survival. When analyzing the different doses within a same period of embryonic development, there was significant difference (p<0.001), in which the higher survival rates were obtained at the lowest concentrations of tebuconazole. The concentration of 200 µg/L was considered highly toxic to the embryos, given that, in less than 24 hours, all embryos had died. The results obtained in this study allow us to conc lude that tebuconazole has the same effects over Danio rerio embryos and adults, causing fragmentation of the genetic material and changes in the behavior of the adults, in addition to reducing embryo lethality.